Removal of Dichloromethane in Up-Flow Anaerobic Sludge Bed Reactors and Methane Production - Ozdemir, Celalettin; Sen, Nejdet; Dursun, Sukru; Kalipci, Erkan (Asian Journal of Chemistry, 2010)
Chlorine has been successfully removed from chlorinated aliphatic compounds under anaerobic conditions. In this research, biological treatment of volatile organic compound (VOC) in highflow anaerobic reactors was carried out. The resistance of micro-organisms was investigated in an upflow anaerobic sludge blanket reactor with an automated control system, using cosubstrate additions, different ratios of organic matter, different hydraulic retention times, stable concentrations of chemical oxygen demand and volatile fatty acids and a range of factors such as pH, alkalinity and temperature (35 ºC) during the anaerobic treatment. Glucose, sodium sulphate, COD, calcium chloride, ammonium bicarbonate, potassium phosphate and methanol were used as co-substrates. The resulting removal rates for dichloromethane and chemical oxygen demand was 60 and 70 %, respectively. The dichloromethane decomposition ratio was 0.136 mg g VSS-1 d-1. The highest methane ratio in the biogas was 64 %. Inhibition concentrations after 24 h were determined as IC50 = 42.6 and IC25 = 16.8.